Implementation of Digital Policy Experimental Analysis in Higher Education on The Level of Graduates' Absorption in Industry - Isna Juwita; Saeful Rohman; Vivid Violin; Akhmad Ramli; Ardhana Januar Mahardhani (SEULANGA SYSTEM PUBLISHER, 2024)
This research aims to analyze the impact of deregulation of the university system on the labor market. We used a sample of 100 people in this research. The research results indicate that without deregulation, most individuals who access university studies would likely only pursue their education. This study uses the year or birth cohort as an exogenous characteristic to implement the instrumental variable strategy. This makes it possible to estimate the causal impact of university education on several employment outcomes, especially wages and labor informality. An admitted university estimates that each year of study will increase the salary. We estimate the cumulative impact of access to university studies. However, the effect of university education on wages turns out to be heterogeneous, depending on individual socio-economic characteristics. The effect tends to be higher in women and individuals in the highest family income quintile. The evidence aligns with other international research regarding the salary premium of university education and its impact on human capital. The results show that for each year of university study, the probability of informality in employment decreases, notably reducing the probability of not having an employment contract. However, we found no significant impact on the probability of not having a pension fund affiliation, suggesting a structural dimension of informality in the labor market that may not be dependent on workers' education level.